The Engineer, the Scientist, and the Philosopher: Conceptual Engineering as an Applied Science - Danka, István (Filozofia Nauki, 2023)
This paper argues that the metaphor of philosophy as conceptual engineering should be better exploited. Conceptual engineers describe their activity as analogous to engineering activities; however, as I will show, some disanalogies can be identified in terms of the purposes of these activities (as described). Engineering has multiple purposes, many of which are external to engineering activity. This applicative part of the metaphor needs further elaboration: conceptual engineering should also pursue purposes external to the profession. First, I shall show how conceptual engineers understand the notion of conceptual engineering and the philosophical methodology this notion implies. Second, I shall further motivate the engineering analogy through the use of metaphilosophical considerations. Third, I shall point to weaknesses in the present form of the analogy between technological and conceptual engineering. I will show that conceptual engineering often seems to copy the work of a physicist rather than a proper engineer. This picture of philosophers as scientists is not as novel as the term “conceptual engineering” would indicate. Engineering is an applied science rather than fundamental research. This characteristic should be better exploited when applied to conceptual work. Finally, I will provide descriptive and normative reasons for the applied science approach to conceptual engineering and respond to some possible objections.